(untitled) (Studia Politica. Romanian Political Science Review, 2025)
Contemporary democracies have evolved over the course of two centuries, stemming from the democratization of representative government following significant revolutions in America (1776) and France (1789). However, it was the aftermath of World War II (1945) that marked a pivotal shift, as democracies embraced liberalism by adopting principles of human rights and the rule of law as foundational requisites. Concurrently, within the most successful Western democracies, the concept of the welfare state emerged as an essential prerequisite for effective democratic governance. This text argues that contemporary democracy constitutes a political regime in which liberal democracy and social democracy are inherently interconnected and indivisible.